The Validity of Patois: An analysis on the Linguistic and Cultural aspects of Jamaican Patois - Adriana Williams (Caribbean Studies Students' Union, 2020)
The purpose of this essay is to debunk the dated Eurocentric notions that dismiss the significance of Jamaican Patois and to argue the validity of the language. To achieve this, research was conducted by exploring various Caribbean literary and linguistic components of the language. However, for the sake of space, only one example per category was analyzed. Patois (also known as Jamaican Creole) is the word used to describe Caribbean speech. Patois, or Patois-based languages, are a part of a continuum of creolized languages (Davidson and Schwartz 48), ranging from pidgins and dialects to full languages. Through socialization and systemization over time, [Jamaican] Patois has developed into a language all its own.